PENGGUNAAN KONSEP ILMU SOSIAL DALAM KONSTRUKSI PEMBELAJARAN SEJARAH KRITIS - Supriatna, Nana (Paramita: Historical Studies Journal, 2012)
This article contains thoughts on the use of social science concepts in the construction of a critical study of history. In view of critical theory, the teaching of history is not only oriented to the past but also the present and contemporary issues. Learning not only highlight the critical history or glorify the greatness of the past but also about the failures and weaknesses in the nation that has been passed that should be corrected in the present. Such learning should be able to include all groups of society as historical figures, including the students in it. History does not only emphasize on national development, but also include local issues are more relevant to students interests. Learning the history of this kind can be presented using a variety of approaches as a way to make students active learners as well as historical actors of his day. This paper criticizing the teaching of history in schools depart from the views essentialis and perenialis and critical importance of developing the teaching of history in accordance with such critical views by using the concept of learning in particular analytical concept.Key words: learning, critical history, curriculumTulisan ini berisi pemikiran tentang penggunaan konsep ilmu sosial dalam konstruksi pembelajaran sejarah kritis. Dalam pandangan teori kritis, pembelajaran sejarah tidak hanya berorientasi pada masa lalu melainkan juga masa kini dan persoalan kontemporer. Pembelajaran sejarah kritis tidak hanya menonjolkan atau mengagungkan kebesaran masa lalu melainkan juga tentang kegagalan dan kelemahan bangsa pada masa yang telah dilewati yang harus diperbaiki pada masa kini. Pembelajaran seperti iniÃÂ  harus dapat memasukkan semua kelompok masyarakat sebagai tokoh sejarah, termasuk para siswa di dalamnya. Sejarah tidak hanya menekankan pada perkembangan nasional, tetapi juga memasukkan isu-isu lokal yang lebih relevan dengan kepentingan siswa. Pembelajaran sejarah seperti ini dapat disajikan dengan menggunakan beragam pendekatan dengan cara menjadikan siswa sebagai pembelajar yang aktif sekaligus sebagai pelaku sejarah pada jamannya. Tulisan ini mengkritisi pembelajaran sejarah di sekolah yang berangkat dari pandangan perenialistis dan esensialistis serta pentingnya mengembangkan pembelajaran sejarah kritis sesuai dengan pandangan kritisÃÂ  antara lain dengan menggunakan pembelajaran konsep khususnya konsep analitis. Kata kunci: pembelajaran, sejarah kritis, kurikulum